2020
DOI: 10.1016/j.jamcollsurg.2019.09.008
|View full text |Cite
|
Sign up to set email alerts
|

WhatsApp Mobile Health Platform to Support Fracture Management by Non-Specialists in South Africa

Abstract: BACKGROUND: Traumatic fractures are common in sub-Saharan Africa, a region with a shortfall of orthopaedic surgeons, and can result in morbidity if not appropriately managed. WhatsApp is an encrypted smartphone application and ubiquitous in sub-Saharan Africa. The objective of this study was to assess the use of WhatsApp as a mobile health platform to support fracture management by non-orthopaedic doctors in Cape Town, South Africa. STUDY DESIGN: A WhatsApp orthopaedic referral group was created between non-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 28 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…12,17,18 The majority of respondents in our survey agreed that WhatsApp consultations have replaced most referrals of patients to other physicians at least once a week. Previous studies have reported even higher rates, 16,19 thus possibly making WhatsApp also a cost-effective tool, saving time, and resources for both physicians and patients by avoiding unnecessary time and travel.…”
Section: Discussionmentioning
confidence: 99%
“…12,17,18 The majority of respondents in our survey agreed that WhatsApp consultations have replaced most referrals of patients to other physicians at least once a week. Previous studies have reported even higher rates, 16,19 thus possibly making WhatsApp also a cost-effective tool, saving time, and resources for both physicians and patients by avoiding unnecessary time and travel.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the recovery of the upper limb motor function is slower, which reduces the ability to do daily life as well as the enthusiasm for training to a certain extent and prolongs the rehabilitation process of the patients. erefore, the rehabilitation of upper limb motor function has become the key of healing treatment for acute stroke patients [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…However, while tech-heavy interventions and super-apps may have a great impact on patient outcomes in our context, most healthcare workers can reflect on the direct benefits that mobile phones and IP services bring them and their patients through the most basic requirement for human endeavour and collaboration: easy, instant communication. Thus interventions, much like Sund et al use of WhatsApp group-chat for data collection, 6,22,23 are available to all healthcare workers and their patients immediately. We should use them wisely for the benefit of all.…”
Section: Editorialmentioning
confidence: 99%